Assessment of the quality of care provided to patients with breast cancer after conservative treatment using the BREAST-Q® - Cecília Oliveira Alferes Gomes Pinto (2022)
Purpose: In breast cancer management not only mortality and surgical morbidity measurements are important but also patient satisfaction indexes. The authors evaluated the satisfaction and health related quality of life (HRQOL) using the Breast Conserving Therapy (BCT) and Breast Reduction (BR) modules of BREAST-Q®. Methods This is a cross-sectional study that analyzed breast cancer patients consecutively submitted to breast surgery between January 2011 to April 2018 using two modules of BREAST-Q®. A total of 968 patients were contacted and we gathered 232 answers: 171 patients answered the BCT module and 61 the BR module. Clinical data were retrieved from patient's medical records. Results Among the 232 questionnaires received, the median scores for Psychosocial Well-Being, Sexual Well-Being and (postoperative) Satisfaction with Breasts for BCT and BR modules were, respectively, 77.0 and 73.5 (p=0.17); 62.0 and 53.0 (p=0.14); 72.0 and 66.0 (p=0.66). The median of adverse effects of radiation in the BCT module was 87.0. The median of satisfaction with outcome in the BR module was 86.0. Both groups of patients revealed high scores of satisfaction with care. For the BCT patients, the Satisfaction with Breasts strongly correlated with Sexual Well-Being, and was moderately correlated with Psychosocial and Physical Well-Being. For the BR patients, the Satisfaction with Outcome strongly correlated with Satisfaction with Medical Team and was moderately correlated with the remaining scales. Conclusion BREAST-Q® is a useful tool to evaluate the satisfaction with the treatment outcomes and the care received from a patient's perspective. In our study, BR yielded similar satisfaction results than BCT.